Effect of infrared belt and hot water bag on the duration of first stage of labor in Primiparous women: A Randomized Clinical Trial - Fatemeh Dastjerd; Fatemeh Erfanian; Ameneh Sazegarnia; Farideh Akhlaghi; Masoumeh Kordi; Habibollah Esmaeili (Mashhad University of Medical Sciences, 2020)
Introduction: Prolonged labor leads to adverse birth outcomes. Thermotherapy is a new non-pharmacological method to reduce duration of labor. Hot water bags and infrared are the methods of thermotherapy. Due to the different mechanism of these two methods and lack of study regarding their comparison, this study was conducted with aim to compare the effect of infrared belt and hot water bag on the duration of the first stage of labor in primiparous women. Methods: This parallel three-group randomized clinical trial was conducted on 150 primiparous women referred to Mashhad Um Al-Benin Hospital in 2019. At first stage of labor, two 20-minute cycles of thermotherapy was performed in the intervention groups by the infrared belt and hot water bag at dilation of 4-5 cm and of 6-7 cm of the cervix. The control group received routine care. Duration of the first stage was assessed from the beginning of 4-5 cm dilation per minute. Data were analyzed by SPSS software (version 25) and Kruskal-Wallis test and one-way analysis of variance. p < 0.05 was considered statistically significant. Results: Mean duration of the first stage of labor was significantly different in the three groups (p <0.001). Mean duration of the first stage of delivery was significantly less in the infrared belt group than the hot water bag group (p <0.001). The infrared belt and hot water bag had no adverse effect on FHR, Apgar score and PPH. Conclusion: The use of infrared belt is an effective way to reduce the duration of the first stage of labor. This method can be used as a complementary method and a non-pharmaceutical treatment method for management of labor.